Etika, Hak & Kewajiban Pelaku Bisnis Transportasi On-Line (GOJEK) Perspektif Bisnis Sharing Economy Syariah - Achmad, Listian Indriyani (Jurnal Ilmiah Ekonomi Islam, 2024)
This paper conducts qualitative research on literature related to describing a form of ethics, rights and obligations of on-line transportation business (GoJek) seen from the perspective of sharia sharing economy business in Indonesia. GoJek, an on-line technology-based transportation service company that uses human and motorcycle modes of transportation, in its business scope has a role that has a major influence on the economy in Indonesia today. GoJek is an economic actor that has a function as a producer that produces services for an information technology-based transportation mode that applies an on-line model in its services. Meanwhile, the government through the Ministry of Transportation (Kemenhub) is an economic actor that functions as a regulator in terms of authorization related to policies that regulate the overall operational scope of all modes of transportation in Indonesia. The rapid development of information technology has changed the shape of the economic system from the conventional one to the form of a sharing economy system. This change also touches on the existence of GoJek's business as an economic actor that functions as a producer, as well as the Ministry of Transportation as a representative of the government which is an economic actor and functions as a regulator of transportation modes in Indonesia. Meanwhile, in the business and economic world, the Islamic economic system is increasingly being sought and applied throughout the world, this can also affect the business conditions of GoJek, including the Ministry of Transportation in responding to its role related to the perspective of the sharia sharing economy. This study finds that there is a form of ethics, rights and obligations of on-line transportation business actors (GoJek) and the role of the government as an economic actor in the perspective of sharing economy sharia.